Comparison of Internal Accuracy of Ceramic Veneered Sintered Metal versus Cast Metal Restoration Upon Different Fabrication Processes - Sripairojn, Sanephume; Juntavee, Niwut; Juntavee, Apa (European Journal of Dentistry, 2025)
One critical factor that influences clinical outcomes of fixed dental restorations is the internal gaps between the restoration and the abutment tooth. However, investigating these gaps in the context of fabrication processes with new technologies is few. This study compared internal accuracy of sintered versus cast metal substructures upon different fabrication techniques, veneered with layering and press-on ceramic, during different construction stages, at different sites of restoration.A total of 96 metal substructures were fabricated with a standardized dimension from four techniques: cast metal with traditionally impressed tooth [CmTt], cast metal with digitally milled wax [CmDw], sintered metal with digitally impressed tooth [SmDt], and sintered metal with digitally impressed stone model [SmDm]. They were further subdivided into two subgroups according to the veneering ceramic used [layered (Pl) and press-on (Pp)]. Internal accuracy was evaluated at gingival, gingiva-axial, axial, axio-occlusal, and occlusal locations using silicone replica, after metal coping (As), degassing (De), opaque application (Op), contouring (Co), and glazing (Gl).Analysis of variance and Bonferroni tests were analyzed for significant differences of internal fit upon different factors (α = 0.05).Significantly different internal accuracy was found upon metal substructures fabrication technique, veneering methods, stages, and sites of restoration (p < 0.05). SmDt and SmDm revealed significantly better fit than CmTt and CmDw (p < 0.05). Pp generated significantly better fit than Pl (p < 0.05). Significantly increasing gaps were found upon stages (p < 0.05). Occlusal and axio-occlusal sites exhibited larger gaps than axial, gingivo-axial, and gingival sites (p < 0.05). However, all groups exhibited clinically acceptable internal accuracy.Increasing internal inaccuracies upon stages of fabrication were noticed, with highly observed at the occlusal and axio-occlusal sites. Sintered metal (SmDt, SmDw) provided better accuracy than cast metal (CmTt, CmDw) while press-on veneering generated better accuracy than the layering method. Ceramic press-on sintered metal was suggested for fabrication restoration.
Keywords: ceramometal; digital impression; internal accuracy; press-on ceramic; sintered metal